Health Education Model in Disaster Situations: Systematic Review - Efa Nugroho; Ayu Istiada; Alfiana Ainun Nisa; Dwi Yunanto Hermawan (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2025)
Background: Communities affected by disasters often lack the necessary knowledge and skills to handle emergency health issues. To address this, effective health education models are essential in enhancing community preparedness and response. To provide effective and efficient recommendations on health education models in disaster situations. Method: This study was a systematic review that gathered multiple studies using the PRISMA flow. Relevant keywords have been used, and articles were collected from various databases, including PubMed, Science Direct, and Scopus. The studies were collected from June to July 2024. Result: Out of 4,363 articles found, 19 were selected for further analysis. Health education in disaster situations can improve individual knowledge and skills to protect themselves, prevent disease, and support public health. This education was conducted in pre-disaster, during disaster, and post-disaster. Conclusion: In the pre-disaster phase, health education focuses on mitigation and preparedness through counseling reinforced by simulations, training, and role-playing. In the disaster phase, media such as digital devices, educational boards, and booklets disseminate information. In the post-disaster phase, health education focuses on restoring and maintaining emotional stability and community safety and addressing trauma-induced stress through health counseling and play. However, the results of this study do not cover the needs of marginalized or special needs groups, so further research is needed to understand how health education models can further adapt to different cultural contexts, especially in the emergency response phase of disasters.